Analysis of The Impact of Destination Digital Tourist Attraction Homestay Accommodation on Visiting Interests to Make Decisions on Visiting Tourists at Mangunan Forest Management Resort - Yoki Anang A W (Syntax Corporation Indonesia, 2021)
This study aims to test the Influence of Digital Destination, Tourist Attraction, Homestay Accommodation On Visiting Interests To Make Decisions to Visit Tourists In Mangunan Forest Management Resort Managed by Notowono Cooperative. The research was conducted on 100 respondents, especially tourists visiting the Mangunan Forest Management Resort area.The results of this study showed: 1). Digital Destination Variables have no significant effect on Visiting Interests with a coefficient value of 0.067 (P Value < 0.05) which is 0.506 2). Coefficient 0.061 (P Value < 0.05) is 0.504 3). Homestay Accomodation variable has a significant effect on Visiting Interest with a coefficient value of 0.596 (P Value > 0.05) 0.000 4). The Digital Destination variable has a significant effect on visiting decisions with a coefficient value of 0.263 (P Value > 0.05) of 0.004. 5). Variable Tourist Attraction to Visiting Decision with a coefficient value of 0.082 (P Value < 0.05) is 0.354. 6). Homestay Accomodation variable has a significant effect on the decision to visit with a coefficient value of 0.244 (P Value > 0.05) of 0.041. The Visiting Interest Variable has a significant effect on visiting decisions with a coefficient value of 0.328 (P Value > 0.05) of 0.002.